2002
DOI: 10.1007/s11606-002-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of active drug use on antiretroviral therapy adherence and viral suppression in HIV-infected drug users

Abstract: Despite a burgeoning literature on adherence to HIV therapies, few studies have examined the impact of ongoing drug use on adherence and viral suppression, and none of these have utilized electronic monitors to quantify adherence among drug users. We used 262 electronic monitors to measure adherence with all antiretrovirals in 85 HIV-infected current and former drug users, and found that active cocaine use, female gender, not receiving Social Security benefits, not being married, screening positive for depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
201
3
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(219 citation statements)
references
References 19 publications
14
201
3
1
Order By: Relevance
“…That stimulant use, including cocaine, may adversely impact medication adherence is generally consistent with the extant literature (e.g., Arnsten et al, 2002;Halkitis, Kutnick, & Slater, 2005;Ingersoll, 2004;Sharpe, Lee, Nakashima, Elam-Evans, & Fleming, 2004). Some have suggested that disruptions to sleep and eating patterns and the increased level of environmental instability attendant to stimulant abuse may drive lower adherence rates (Reback, Larkins, & Shoptaw, 2003).…”
Section: Discussionsupporting
confidence: 66%
“…That stimulant use, including cocaine, may adversely impact medication adherence is generally consistent with the extant literature (e.g., Arnsten et al, 2002;Halkitis, Kutnick, & Slater, 2005;Ingersoll, 2004;Sharpe, Lee, Nakashima, Elam-Evans, & Fleming, 2004). Some have suggested that disruptions to sleep and eating patterns and the increased level of environmental instability attendant to stimulant abuse may drive lower adherence rates (Reback, Larkins, & Shoptaw, 2003).…”
Section: Discussionsupporting
confidence: 66%
“…There is considerable evidence of the link between psychological distress [17][18][19][20][21], substance use [17][18][19][20][21][22][23][24], and negative attitudes and beliefs about the efficacy of antiretroviral medications [26][27][28][29][30][31] and nonadherence to antiretroviral therapy, and the impact of psychological distress is often compounded by co-occurring substance abuse [51,52]. Our study indicates that by facilitating changes in these modifiable barriers to adherence, it may also be possible to improve adherence as well.…”
Section: Resultsmentioning
confidence: 74%
“…Among the most frequently cited correlates and predictors of nonadherence to antiretroviral therapy in the published literature are dimensions of psychological distress such as depression, anxiety, stress and coping [17][18][19][20][21]; active substance use [22][23][24][25]; and perceptions and beliefs regarding the efficacy of antiretroviral medications [26][27][28][29][30][31]. However, few of these studies have looked at temporal trends in adherence [32][33][34] using longitudinal methods [35][36][37][38][39][40][41][42] and even fewer have investigated whether changes in these adherence barriers result in concomitant changes in adherence behavior over time [39,41,43].…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to HAART is important as missed dosages can affect viral replication and can lead to drug resistance (Ho et al 1995;Low-Beer et al 2000). Several studies indicate that factors such as current substance use and unstable housing impede medication adherence and viral suppression (Arnsten et al 2002;Duran et al 2001;Knowlton et al 2001;Lucas et al 2001;O' Connell et al 2003;Pulvirenti et al 2003;Turner et al 2001), leading to more likely transmission of multidrug resistant strains of HIV (Little et al 2002).…”
Section: Introductionmentioning
confidence: 99%